2002
DOI: 10.1248/bpb.25.823
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Plasma Dihydroxyphenylacetic Acid Levels in Decapitated Mice after Exposure to Various Stresses.

Abstract: This study investigated changes in plasma levels of the dopamine metabolite dihydroxyphenylacetic acid (DOPAC) in decapitated mice in response to the variable stresses of restraint, restraint and water immersion, and foot shock. DOPAC levels, but not norepinephrine (NE) and epinephrine (EPI) levels, increased upon exposure to these stresses. Plasma DOPAC levels measured using the decapitation method in rats were then compared with those measured using the catheter method. The NE and EPI levels in plasma measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It is known that plasma DA and DOPAC levels depend on the activity of tyrosine hydroxylation in sympathetic neurons. 26,27) Clearly, heat stress would have few effects on the sympathetic nerves. On the other hand, it is reported that heat stress using severe conditions, such as 42°C, increased plasma NE and epinephrine levels in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that plasma DA and DOPAC levels depend on the activity of tyrosine hydroxylation in sympathetic neurons. 26,27) Clearly, heat stress would have few effects on the sympathetic nerves. On the other hand, it is reported that heat stress using severe conditions, such as 42°C, increased plasma NE and epinephrine levels in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of Plasma Dopamine (DA) and Dihydroxyphenylacetic Acid (DOPAC) Levels Mice were exposed to 37°C 85% RH or RWI for 10, 20, 40, 80 and 160 min. The concentrations of DA and DOPAC in the plasma were assayed using HPLC with electrochemical detection (ECD) after batch alumina extraction as previously described 26) with the following modifications. For the HPLC, the separation column was a Biophase ODS IV (3 mm, 4ϫ110 mm, BAS, Tokyo, Japan) and the mobile phase consisted of 50 mM citrate buffer, pH 3.2, containing 8% acetonitrile, 1 mM EDTA and 0.3 mM sodium octylsulfate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on such responses have been conducted using cultured cells or whole organisms, including a shift of temperature, exposure to chemicals, irradiation and lack of nutrients. Here, we report the responses to stress occurring in the brain of mice subjected to cage‐restraint and water‐immersion, which are methods that have been used widely in psychophysiological analyses [1,2]. Recently, Hayashi et al [3] reported that diazepam, an anti‐depressant drug, blocked the induction of a stress‐response marker in mouse brain under psychophysiological stress, suggesting a psychological component of the stress.…”
Section: Introductionmentioning
confidence: 98%